Seamus Heaney and medieval poetry - McCarthy, Conor (D.S. Brewer ; Boydell & Brewer, 2008)
"Seamus Heaney's engagement with medieval literature constitutes a significant body of work by a major poet that extends across four decades, including a landmark translation of Beowulf. This book, the first to look exclusively at Heaney's engagement with the poetry of the Middle Ages, examines both Heaney's direct translations and his adaptation of medieval material in his original poems. Each of the four chapters focuses substantially on a single major text: Sweeney Astray (1983), Station Island (1984), Beowulf (1999), and The Testament of Cresseid (2004). The discussion examines Heaney's translation practice in relation to source texts from a variety of languages (Irish, Italian, Old English, and Middle Scots) from across the medieval period, and also in relation to Heaney's own broader body of work. It suggests that Heaney's translations and adaptations give a contemporary voice to medieval texts, bringing the past to bear upon contemporary concerns both personal and political."--Jacket